Dopamine, urges to smoke, and the relative salience of drug versus non-drug reward - Freeman, Tom P. (Soc Cogn Affect Neurosci, 2015)
When addicted individuals are exposed to drug-related stimuli, dopamine release is thought to mediate incentive salience attribution, increasing attentional bias, craving and drug seeking. It is unclear whether dopamine acts specifically on drug cues versus other rewards, and if these effects correspond with craving and other forms of cognitive bias. Here, we administered the dopamine D(2)/D(3) agonist pramipexole (0.5 mg) to 16 tobacco smokers in a double-blind placebo-controlled crossover design. Visual fixations on smoking and money images were recorded alongside smoking urges and fluency tasks. Pramipexole attenuated a marked bias in initial orienting towards smoking relative to money but did not alter a maintained attentional bias towards smoking. Pramipexole decreased urges to smoke retrospectively after the task but not on a state scale. Fewer smoking words were generated after pramipexole but phonological and semantic fluency were preserved. Although these treatment effects did not correlate with each other, changes in initial orienting towards smoking and money were inversely related to baseline scores. In conclusion, pramipexole can reduce the salience of an addictive drug compared with other rewards and elicit corresponding changes in smoking urges and cognitive bias. These reward-specific and baseline-dependent effects support an ‘inverted-U’ shaped profile of dopamine in addiction.